Exploration of biotic inducers through seed infiltration technique for the management of phyllody in sesame caused by Candidatus Phytoplasma : Exploration of biotic inducers through seed infiltration technique for the management of phyllody in sesame caused by Candidatus Phytoplasma - M KOWSALYA; D DURGADEVI; R KAVITHA; L KARTHIBA; S VARANAVASIAPPAN; L RAJENDRAN; G KARTHIKEYAN (Journal of Oilseeds Research, 2023)
This study aimed to evaluate the efficacy of biotic inducers for the management of phyllody disease in sesame, as well as in analyzing the defense enzyme activity. The field trial experiments were conducted with the biotic inducers [salicylic acid (SA), methyl jasmonate (MeJA), and beta amino butyric acid (BABA)] in individually (50 ppm, 100 ppm and 150 ppm) and in combination. Concerning biotic inducers, SA 50 / 100 ppm pre-seed treatment and exogenous application at 30th, 45th and 60th DAS resulted in no/less phyllody disease incidence and added significant value by increasing defense enzyme activity (PO, PPO, PAL and SOD).